Ways of thinking siswa dalam menyelesaikan masalah pola bilangan non rutin: Suatu penelitian fenomenologi hermeneutik - Aiyub Aiyub (Journal of Didactic Mathematics, 2023)
This study was conducted with the aim of investigating and exploring students' ways of thinking (WoT) in solving non-routine number pattern problems. This study used a qualitative method with a hermeneutic phenomenological approach with grade 8 students at a junior high school in Banda Aceh. To achieve the research objectives, data collection was carried out using a written test instrument with a number pattern on a 4-digit palindrome, structured documentation, and clinical interviews. The results of the study show that students' WoT in solving non-routine number pattern problems is that there are four approaches used in solving non-routine problems, namely: first, determining the special case; second, determining the pattern; third, using a mathematical model; and fourth, using a similar problem. The subject of critical reflection uses the three WoTs above except for using similar problems. The subject of explicit reflection uses the three approaches above except for using a mathematical model. While Subjects who cannot solve the problem only use the strategy of identifying special cases. Another finding is that the subject of critical reflection tends to use different strategies from those given by the teacher, is unique, and gives reasons for algebraic forms. In contrast, explicit reflection subjects tend to be less flexible in using strategies and tend to use inductive or arithmetic reasons. To support students in their ability to pattern and think algebraically, teachers must accustom students to solving non-routine mathematical problems in various contexts of learning by using number patterns.